Mary as the Ark of the Covenant in the Scene of the Visitation (Luke 1:39-56) Reconsidered - Kozłowski, Jan M. (Warszawskie Studia Teologiczne, 2018)
In his “Structure et théologie de Luc I-II” from 1957, René Laurentin advanced the view that the figure of Mary is to be interpreted as a new Ark of the Covenant in the scene of the Visitation (Luke 1:39-56). This interpretation is based primarily on an intertextual reference to 2 Sam 6:1-11. Still, Laurentin’s thesis did not resonate with New Testament scholars. In the present paper, it is shown that recent observations according to which the embryo in Mary’s womb is to be identified as yhwh Himself offer new evidence for Laurentin’s thesis.